HAK HADANAH PASCA PERCERAIAN MENURUT IBN HAZM - Mustori Mustori; Robi’ah Robi’ah; Rohmani Rohmani (Hikmah: Journal of Islamic Studies, 2022)
AbstractObjectives of research is to know child care of law (hadanah) post divorce the according Ibn Hazm. The research was using qualitative method by approaching normative, besides the kind of method is using qualitative by describing and explanning by library research and data analyze. The result of research by child of cultivation (hadanah) postdivorce the according Ibn Hazm there is mother hand. The mother has the righter to take care of children it than him father, but Ibn Hazm have a different opinion about fall or not in child of cultivation if the mother did get married father. The according Ibn Hazm that is if the mother give burden to cultivate a child in fact get married again, there for not fallin the right cultivation. If husband be trusted in his religion and can be follower to wive there for have rules be permitted.  AbstrakPenelitian ini bertujuan menggali lebih lanjut pendapat ibn Hazm tentang hak asuh anak (hadanah) pasca perceraian. Penelitian ini tergolong pada jenis penelitian pustaka (library Research). Menggunakan metode kualitatif dengan pendekatan normative, penelitian ini menunjukkan bahwa pemeliharaan anak (hadanah) pasca perceraian menurut Ibn Hazm berada di tangan ibu. Ibu lebih berhak mengasuh anak tersebut di banding ayah dan pihak lainnya. Mayoritas ulama berpendapat gugurnya hak asuh anak bagi si ibu yang telah menikah lagi. Berbeda dengan pendapa Ibn Hazm yang berpendapat tidak gugurnya hak ibu yang sudah menikah lagi terhadap untuk mengasuh anaknya, dengan syarat si ibu dan suaminya dapat dipercaya dalam hal agama dan dunianya.